(untitled) (XXI Century. Spanish Literature and Culture, 2008)
In this article I study the work by Manuel Rivas: EL Lápiz del Carpintero from a post-colonialist point of view, with special consideration to the link established between the prison guard, Herbal, and the prisoner, Da Barca. This relationship is parallel to the relationship given between the colonizer and the colonized, as Cesáire´s and Fernando Ortiz´s -among others- ideas state. Likewise, following Kristeva´s and Spivak´s theories about “the stranger” and “the subaltern”, I study the process of the novel, through which different voices that had been silenced during the Spanish Civil War come to life, incarnated in a pencil that talks to the guard as his own conscience.